Absorption, distribution, metabolism and excretion of molidustat in healthy participants. Issue 3 (20th April 2020) - Lentini, Silvia; van der Mey, Dorina; Kern, Armin; Thuss, Uwe; Kaiser, Andreas; Matsuno, Kumi; Gerisch, Michael
Abstract: The absorption, distribution, metabolism and excretion of molidustat were investigated in healthy male participants. In study 1, a mass balance study, radiolabelled molidustat 25 mg (3.57 MBq) was administered as an oral solution (n = 4). Following rapid absorption, molidustat‐related radioactivity was predominantly distributed in plasma rather than in red blood cells. The total recovery of the administered radioactivity was 97.0%, which was mainly excreted renally (90.7%). Metabolite M‐1, produced by N‐glucuronidation, was the dominant component in plasma (80.2% of the area under the concentration‐time curve for total radioactivity) and was primarily excreted via urine (~85% of dose). Only minor amounts of unchanged molidustat were excreted in urine (~4%) and faeces (~6%). Study 2 investigated the absolute bioavailability and pharmacodynamics of molidustat (part 1, n = 12; part 2, n = 16). Orally administered molidustat immediate release tablets had an absolute bioavailability of 59%. Following intravenous administration (1, 5 and 25 mg), total body clearance of molidustat was 28.7‐34.5 L/h and volume of distribution at steady state was 39.3‐50.0 L. All doses of molidustat transiently elevated endogenous erythropoietin levels, irrespective of the route of administration. Molidustat was considered safe and well tolerated at the administered doses.